GERARD GENETTE'S NARRATIVE STRUCTURE IN FIHI MA FIHI NOVEL BY JALALUDIN RUMI - Qulub, Muhammad Farihul; Rizky, Muhammad Roudho (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2023)
Fihi Ma Fihi is a sufism novel that transmits in prose. The novel explains the moral and scientific issues of Sufism, accompanied by Qur'anic and hadith explanations related to social values and spirituality. The narrative of the novel is complex since the novel portrays an explication of the reality in life. This study aims to analyze the narrative structure in Fihi Ma Fihi novel based on the perspective of Gerard Genette, which includes the analysis of order, duration, frequency, mode, and sound reflected in the novel using a descriptive qualitative method. The main data source used is Fihi Ma Fihi novel by Jalaludin Rumi. The results found five aspects in the novel: order in the form of a sequence of story travel, duration in the form of time differences, frequency in the form of relationships in the form of an event, modes in the form of prominent roles for characters, and speech or sounds in the form of language messages seen based on any relationship.